2018
DOI: 10.1111/crj.12770
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and medication belief in patients with pulmonary arterial hypertension or chronic thromboembolic pulmonary hypertension: A nationwide population‐based cohort survey

Abstract: Treatment adherence is relatively high but still needs improvement. The multi-disciplinary PAH team should, together with the patient, seek strategies to improve adherence and prevent concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 26 publications
5
23
1
Order By: Relevance
“…The present study used a strict method for treatment adherence, allowing only one missed daily dosage per month to be categorized as low adherence. In support of this method, the overall adherence to PAH-treatment found in the study was in good concordance with the self-reported treatment adherence of 57% from the Swedish PAH and CTEPH population that has been published earlier [7]. The patient's perception of adverse side effects that might occur, has been shown to affect the patient's decisions weather to take the drugs as prescribed or not [15,16].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The present study used a strict method for treatment adherence, allowing only one missed daily dosage per month to be categorized as low adherence. In support of this method, the overall adherence to PAH-treatment found in the study was in good concordance with the self-reported treatment adherence of 57% from the Swedish PAH and CTEPH population that has been published earlier [7]. The patient's perception of adverse side effects that might occur, has been shown to affect the patient's decisions weather to take the drugs as prescribed or not [15,16].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, it is important to address the patients concerns about a treatment, both at the time of first prescription as well as at subsequent meetings with the patient [18,19]. As shown in the present study, as well as in earlier studies, the longer time since diagnosis that has elapsed, the lower is the adherence to treatment [7,8].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations